Household incomes and redistribution in the European Union: Quantifying the equalising properties of taxes and benefits - Herwig Immervoll; Horacio Levy; Christine Lietz; Daniela Mantovani; Cathal O'Donoghue; Holly Sutherland; Gerlinde Verbist (Institute for Advanced Studies (IHS), 2006)
The systems of direct taxes and cash benefits in the Member States of the European Union vary considerably in size and structure. We explore their direct impacts on cross-sectional income inequality (termed redistributive effect for the purpose of this paper) using EUROMOD, a tax-benefit microsimulation model for the European Union. This relies on harmonised household micro-data representative of each national population together with simulations of entitlements to cash benefits and liabilities for taxes and social contributions. It allows us to draw a more comprehensive - and comparable - picture of the combined effects of transfers and taxes than is usually possible. We decompose the redistributive effect of taxbenefit systems to assess and compare the effectiveness of individual policies at reducing income disparities. We derive results for the 15 old members of the European Union and present them for each country separately as well as for the EU-15 as a whole.
Keywords: C81; D31; H22; H55; 330; income inequality; redistribution; microsimulation; European Union; Haushaltseinkommen; Einkommensverteilung; Einkommensumverteilung; EU-Staaten; Verteilungswirkung